Working together to face humanity's greatest threats: Introduction to the Future of Research on Catastrophic and Existential Risk. (September 2018) - Currie, Adrian; Ó hÉigeartaigh, Seán
Highlights: The special issue brings together a wide range of research on existential and catastrophic risk. Research into existential and catastrophic risk is increasingly multi-disciplinary and broad in scope. We consider how existential risk is conceptualized as well as challenges in communication, responsibility and epistemology.